Learning from the Humility and Sacrifice of Christ in Easing Conflict - Marde Christian Stenly Mawikere; Sudiria Hura; Jean Calvin Riedel Mawikere; Daniella Beauty Melanesia Mawikere (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This study aims to explore the significance of Christ's humility and sacrifice, particularly through His emptying and death on the cross, and its implications in alleviating interpersonal and social conflicts. Adopting a qualitative approach, the study employs literature review and content analysis methods to examine biblical texts, theological works, and modern theories on conflict and reconciliation. The research focuses on how the principles of Christ's humility and sacrifice, exemplified in His self-emptying action to serve humanity, can be applied to resolve conflicts and restore relationships between individuals. The findings of this study indicate that Christ's teachings provide a relevant model for reconciliation and peacebuilding, both in personal life and on a broader social scale. The novelty of this research lies in linking the theological values of Christ with contemporary conflict resolution theories, offering new insights into the role of humility and sacrifice in addressing social tensions. This study contributes to understanding the relevance of Christ's teachings in the context of current conflicts.